Intelligences and Creativity: Theory, Metaphor, Experience - D'Antoni, Maurizia (2004)
Indeed, knowing how the "emotional brain" evolved, that is, the part of the brain that is the seat of emotional responses in human beings, allows us to better understand these functions; what is interesting without a doubt is that this part of our brain is born with an olfactory function (Le Doux, 1996).